Problem-based earning versus lecture-based learning for Gestational Diabetes Mellitus diagnosis in health care centers - Mahnaz Boroumand Rezazadeh; Seyed Reza Mousavi; Tina Zeraati; Maliheh Dadgarmoghaddam; Nazila Zarghi; Masoumeh Mirteimouri; Tayebeh Seyfizadeh (Mashhad University of Medical Sciences, 2024)
Background: Gestational diabetes mellitus (GDM) is the most common medical complication of pregnancy, resulting both maternal and fetal/neonatal negative consequences. Since health care staff in health care centers, including general practitioners and midwives encounter the condition at the first line, they should be well trained about it. This study aimed to investigate whether the problem-based learning (PBL) or the lecture-based learning (LBL) method is preferred regarding medical pedagogy. Method: A descriptive test about GDM screening and diagnosis was given to the health care staff of 10 health care centers in Mashhad. 66 individuals with the lowest points were involved in the study in two groups of 33. The first group joined a lecture-based educational program about GDM, while the other group were trained using the PBL method. After a week, a test was given to them, and the results were compared between the two groups.Results: The scores of the gestational diabetes diagnosis test in both groups increased significantly after the training (change from 3.50±1.40 to 6.20±1.51 in the PBL group, P<0.001; and 3.32±1.64 to 5.58±1.66, P<0.001). There was no significant difference in the results between the two groups (P=0.13).Conclusion:  The results of PBL educational programs about GDM are not superior to the results of the LBL method.